Potret Perempuan Jawa dalam Makna Asosiatif Diakronis Peralatan Rumah Tangga Tradisional - Muhammad Suryadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This study aims to reveal the portrait of Javanese women in Java in the past. This research was conducted using an associative-diachronic meaning approach. The disclosure of phenomena is carried out by describing each lexicon of traditional household tools based on their associative meaning. The lexicon is analyzed based on its associative meaning based on the local wisdom of Javanese culture. Diachronic studies to explore the wealth of local wisdom stored in traditional household appliances as a legacy from the past. The level of urgency of this research is the shift and replacement of the use of traditional household tools to tools made from plastic and metal. This phenomenon will lead to abandonment of traditional household appliances and being forgotten. The research location is in Kudus Regency which is part of the north coast of Central Java. The data collection methods used were in-depth interviews and document data extraction. Metode pengumpulan data yang digunakan adalah wawancara mendalam dan ekstraksi data dokumen. The data analysis method used was to sort out the semantic elements and determine the associative meaning of the lexicon of traditional household appliances. The novelty of the findings lies in the design of descriptions of associative semantic elements in traditional household appliances based on local wisdom.